Complexation study of indium (III) bromide and strontium (II) chloride with chalcone's derivatives. - Azura, Jaini. (Universiti Malaysia Sarawak (UNIMAS), 2005)
The synthesis and spectroscopic characterization of indium(III) and strontium(II) complexes with chalcone's are reported in this thesis. Tautomerization occurred before the coordination of chalcone (l-phenyl-3(4-hydroxy-phenyl)-propenone) to strontium(II) chloride and indium(III) bromide. For 1 (4-hydroxy-phenyl)-3-phenyl-propenone, the complexation occurred at the deprotonated oxygen atom from the hydroxyl group. The ligands appeared as a uninegative monodentate fashion for all the synthesized indium(III) and strontium(II) complexes. The Sr:ligand ratio is 1: 1 for all Sr(II) complexes forming three-coordinated molecule in trigonal planar geometry. The In:ligand ratio is 1:3 in complexation with 1phenyl- 3(4-hydroxy-phenyl}-propenone forming a six-coordinated molecule in octahedron structure and 1: 1 ratio in complexation of indium(III) with 1 (4-hydroxy-phenyl)-3-phenylpropenone. The reactions of chalcone's with indium(III) bromide and strontium(lI) chloride gave a new coordination mode of In-O and 8r-0 bonds, respectively.